Towards higher sense of presence: a 3D virtual environment adaptable to confusion and engagement - Silva Pedro, T. (2021)
Virtual Reality scenarios where emitters convey information to receptors can be used as a tool for distance learning and to enable virtual visits to company physical headquarters. However, immersive Virtual Reality setups usually require visualization interfaces such as Head-mounted Displays, Powerwalls or CAVE systems, supported by interaction devices (Microsoft Kinect, Wii Motion, among others), that foster natural interaction but are often inaccessible to users. We propose a virtual presentation scenario, supported by a framework, that provides emotion-driven interaction through ubiquitous devices. An experiment with 3 conditions was designed involving: a control condition; a less confusing text script based on its lexical, syntactical, and bigram features; and a third condition where an adaptive lighting system dynamically acted based on the user’s engagement. Results show that users exposed to the less confusing script reported higher sense of presence, albeit without statistical significance. Users from the last condition reported lower sense of presence, which rejects our hypothesis without statistical significance. We theorize that, as the presentation was given orally and the adaptive lighting system impacts the visual channel, this conflict may have overloaded the users’ cognitive capacity and thus reduced available resources to address the presentation content.